Análise de desempenho de uma rede sem-fio de baixa potência e longo alcance para a internet das coisas - Molano Ortiz, Fernando (2018)
Nowadays, the dissemination of information originating at the digitization of different physical processes involving sensing, processing and communication in smart cities has produced multiple challenges related to the inclusion of electronic devices in the society as well as the generation of big data. Thus, devices can send information that is captured and processed over large areas, they become a challenge because of the number of devices that need to be deployed across a network. Different wireless technologies can be used. This work evaluates LoRa communication technology, a recent approach of low-power long-range networks. The communication performance of LoRa nodes is analyzed considering the throughput, packet loss rate, signal strength, and signal-to-noise ratio. The objective is to characterize the behavior of the LoRa network as a function of the distance between the nodes, but also as a function of the spreading factor, a configurable modulation parameter in LoRa technology. The results are obtained from practical measurements in the campus of UFRJ. An experimental prototype was implemented in different environments, showing that distance variations and interference sources affect the network performance. For example, the experiments show that increasing the spreading factor from SF7 to SF11 reduces the loss rate of transmissions over 2 km distance, however, producing longer communication delay and lower data transfer rate.